Isolation, molecular characterisation and bioprospecting of actinobacteria from Greenwich Island and Dee Island, Antarctica - Chu, Pek Lim (2014)
Antarctica is a pristine region on Earth that is well known for its extreme environmental conditions. The limited distribution of microbes shaped by the biogeography of Antarctica might promote the development of endemic microbial populations and evolution of endemic taxa with unique cold-adaptation and survival strategies in the harsh environment. Actinobacteria is one of the dominant soil inhabitants in the Antarctic continent. A total of 15 soil samples were collected from different sites of Greenwich Island and Dee Island to investigate the distributions of actinobacteria in the soil and to reveal their biosynthesis potential. Molecular screening for actinobacteria was achieved by amplifying the large insert stretch specifically found in the 23S rRNA gene of Actinobacteria. A selective isolation approach enabled 36 actinobacteria isolates of ten different genera to be successfully recovered. The highest diversity and abundance of actinobacteria was harboured in slightly alkaline soil (62.5%), compared to the moderately alkaline soil (26.8%) and extremely alkaline soil (10.7%). The major representatives of Actinobacteria belong to the genera Streptomyces, Micrococcus, Kocuria and Micromonospora. Phylogenetic analysis revealed that one presumptive new species of Micromonospora was isolated (98.8% 16S rRNA gene sequence similarity). Through the PCA analysis, water availability which serves as a dynamic source for the interactions of microbes was examined as the principal factor that shaped the distribution of actinobacteria from Greenwich Island and Dee Island. The presence of the biosynthetic systems polyketide synthase (PKS) and non-ribosomal peptide synthase (NRPS) in the genomes of the actinobacteria isolates indicated their great biosynthesis potential. In the expression analysis, the bioactive compounds recovered in ethyl acetate extracts were showing antibacterial activity against a broad spectrum of Gram-positive and Gram-negative pathogenic bacterial strains. The best group of antibacterial producers was the actinobacteria isolated from highly alkaline soil (>pH8.5), which exhibited 19.5% higher antibacterial activity than the next group of isolates from moderately alkaline soil (pH 7.9-8.4). The random amplified polymorphic DNA (RAPD) analysis was capable of detecting the intra-specific genetic variations among the 11 Streptomyces species and generated a specific cluster of Streptomyces albidoflavus. Other than taxonomic classification, RAPD is also capable of segregating the actinobacteria isolates into clusters having specific antibacterial patterns. Antarctica has emerged as a natural reservoir of actinobacteria with great biosynthesis potential for bioprospecting.